GROUNDWATER FLOW SYSTEM OF BANDUNG BASIN BASED ON HYDRAULIC HEAD, SUBSURFACE TEMPERATURE, AND STABLE ISOTOPES - Robert M. Delinom; Ade Suriadarma (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2010)
ABSTRACT To recognize the groundwater flow system in the Bandung Basin, two main methods of regional groundwater flow delineation were employed: hydraulic heads and tracers. Two different environmental tracers, i.e. subsurface temperature and stable isotope were applied. The measured temperatures and stable isotope compositions from 19 observation wells lead  to the recognition of three types of flow systems within the Bandung Basin i.e., shallow, intermediate and deep groundwater flow system. The recharge area is located in the hills and upland which form the periphery of the plain. The summit area of the southern mountainous complex might have represented the highest recharge area No indication was found for water being recharged at higher elevation in the northern part of the basin which means the recharged water in the Mount Tangkuban Parahu area did not reach the Bandung Plain. This study clearly demonstrates the usefulness of these environmental tracers and hydraulic head measurement in identification of the groundwater flow system of a certain area.